Diversity of root nodule bacteria isolated from common bean (Phaseolus vulgaris L.) in Cuba: effect of Rhizobium – PGPR inoculation and IAA synthesis on development of bean genotypes - Colás Sánchez, Ariany (Universidad Central “Marta Abreu” de Las Villas. Facultad de Ciencias Agropecuarias. Departamento de Agronomía, 2014)
Common bean (Phaseolus vulgaris L.) is the most important food legume for the direct human consumption in the world and particularly in many parts of Latin America and Africa. Symbiotic nitrogen fixation (SNF) through association with root-nodulating rhizobia effectively contributes to an improved crop production and is an ecologically sound and low cost strategy to improve productivity in common bean cultivation. However, the amount of nitrogen fix by common bean in the field is often low compared to the SNF capacity of beans under optimal conditions and compared to other legumes. The success of SNF in bean cultivation is strongly influenced by prevailing environmental conditions. Further research to improve the efficiency and stability of SNF in bean cultivation is needed. In the rhizosphere and in their interaction with plants, rhizobia encounter many different plant compounds, including phytohormones like auxins, giberelinis and cytokinins. Several steps of rhizobia-legume interaction are monitored by these phytohormones, especially nodule formation. However, the exact role of bacterial IAA (indole-3-acetic acid) in nodule formation and functioning is still unknown. This study focuses on the characterization of the nodule inhabiting organisms by the application of molecular techniques and to investigate the agronomic implication of the legume-Rhizobium-Plant growth promoting rhizobacteria (PGPR), as well as to determine the possible role of bacterial IAA production in modulation of nodulation. In total, 20 gram negative strains were isolated from root nodules of common bean in the central region of Cuba. By partial sequencing of the 16S rRNA gene, six different genera, i.e. Arthrobacter, Chryseobacterium, Enterobacter, Stenotrophomonas, Pseudomonas and Rhizobium were recovered. Rhizobium was the only genus containing differences at the species level. In total four Rhizobium species were identified (Rhizobium sp., R. etli, R. pisi and R. radiobacter). Of which, only R. pisi and R. etli species nodulated the host plant. The phenotypic characterization showed the beneficial effect of the R. etli and R. pisi on bean genotypes, by increasing the nodulation, growth parameters and N fixation at early stage of common bean plants. Under field trial conditions, the nodulation, growth parameters and yield were stimulated significantly for BAT-477 as compared with the genotypes BAT-304, ICA Pijao and DOR-364, upon Summary ii inoculation with the isolated Rhizobium strains. A survey among 60 local bean farmers showed that farmers use microbial inocula as well as other organic fertilizers when they have access to them. Resistance to pests, good taste which was always associated to black color and resistance to diseases, were included as preferential characteristic for choosing a new variety. Combinations of Rhizobium-PGPR were evaluated under different growth conditions, using two contrasting genotypes (BAT-477 and DOR-364). The results highlight the interaction between genotype, bacterial inoculant and environmental soil conditions. It was observed that native Rhizobium-Pseudomonas co-inoculation as compared to single Rhizobium inoculation increased the nodulation and growth parameters in greenhouse experiments as well as in a field trials. The combination Rhizobium-Pseudomonas showed the best results in yield in both genotypes and BAT-477 performed significantly better than DOR-364. In addition, all nodule endophytic bacterial strains showed plant growth promoting activities, the production of indole-3-acetic acid (IAA) resulted common to all of them, the synthesis of siderophores and phosphate solubilization was only produced for Pseudomonas strains. These results indicate a potential role of isolated bacterial in improving plant growth. Several lines of evidence suggest a role for phytohormones in root nodule development. In our study R. pisi R40983 (ipdC) transconjugant showed major nodule stimulation in common bean plants as well as major IAA production principally during the stationary growth phase. Based on the nodulation experiment, it was demonstrated that the introduction of these recombinant ipdC construct could improve nodulation. These findings contribute to the understanding of the interplay between Rhizobium, PGPR and the plant host under different soil conditions. Importantly, co-inoculation with R. pisi and P. monteilii could be an effective biofertilization strategy for common bean production. From this study, some important recommendations can be drawn on how to improve bean productivity in this
Keywords: Rhizobium; Phaseolus Vulgaris L.; Frijol; Bacterias fijadoras de Nitrógeno